2000
DOI: 10.2176/nmc.40.432
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Meninges in the Posterior Cranial Fossa. Magnetic Resonance Imaging and Histological Correlation. Case Report.

Abstract: A 58-year-old female presented with a rare case of intracranial solitary fibrous tumor (SFT) manifesting as progressive ataxic gait and hearing loss on the left persisting for 6 months with recent symptoms of increased intracranial pressure. Computed tomography demonstrated a large isodense irregular-shaped mass in the left posterior cranial fossa. T2-weighted magnetic resonance imaging showed two components appearing as very low intensity and high intensity. Extreme-lateral suboccipital craniotomy was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 5 publications
6
37
0
Order By: Relevance
“…This feature on T2-weighted images has the appearance of a "black-and-white" mixed pattern or ying-yang pattern. Nawashiro et al 15 suggested that the imaging findings are due to collagenous hypocellular regions and hypercellular regions with "staghorn" vascular pattern capillaries, which, respectively, correspond with the area of low signal intensity and the area of high signal intensity on T2-weighted images. Most solid portions of the lesions showed heterogeneous strong enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature on T2-weighted images has the appearance of a "black-and-white" mixed pattern or ying-yang pattern. Nawashiro et al 15 suggested that the imaging findings are due to collagenous hypocellular regions and hypercellular regions with "staghorn" vascular pattern capillaries, which, respectively, correspond with the area of low signal intensity and the area of high signal intensity on T2-weighted images. Most solid portions of the lesions showed heterogeneous strong enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Moreover, there is only limited description of imaging features of SFT affecting the intracranial region. 15,16 The purpose of this study was to describe the MR imaging, CT imaging, and angiographic features of pathologically proven ISFT and to identify imaging characteristics.…”
mentioning
confidence: 99%
“…The majority of intracranial SFTs had a dural origin, whereas one third of spinal SFTs had a dural attachment. 2,8,10,13) Since the present tumor was continuous with the spinal nerve root and not attached to the dura mater, the origin seemed to be the pial or vascular tissue of the nerve root.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, SFT has been found in the central nervous system (CNS). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] We report a case of intradural extramedullary SFT of the thoracic spine.…”
Section: Introductionmentioning
confidence: 99%
“…5,14) MR imaging shows SFT as isointense on T 1 -weighted images, hyperintense on T 2 -weighted images, and homogeneous enhancement after intravenous administration of gadolinium. 11,17) The clinical behavior of SFT is generally considered to be benign if the tumor is totally removed. 12) Recently, stereotactic radiosurgery as adjuvant treatment for residual SFT has been advocated, but experience with more cases is needed.…”
Section: Discussionmentioning
confidence: 99%